A mini review on production of pluripotency factors (Oct4, Sox2, Klf4 and c-Myc) through recombinant protein technology - Marpaung, David Septian Sumanto; Sinaga, Ayu Oshin Yap (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2020)
The four transcription factors OCT4, SOX2, KLF4 and c-MYC are highly expressed in embryonic stem cells (ESC) and their overexpression can induce pluripotency, the ability to differentiate into all cell types of an organism. The ectopic expression such transcription factors could reprogram somatic stem cells become induced pluripotency stem cells (iPSC), an embryonic stem cells-like. Production of recombinant pluripotency factors gain interests due to high demand from generation of induced pluripotent stem cells in regenerative medical therapy recently. This review will focus on demonstrate the recent advances in recombinant pluripotency factor production using various host.